(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
This experiment was carried to investigated the influence of using 3 different feed restriction systems with or without adding the dietary anise and fenugreek on productive performance of broiler chickens during the early age (2 and 3 weeks). It has been used 400 unsexed chicks (Ross 308) - one day old which distributed randomly into 10 treatments (40 chicks / treatment(assigned into 2 replications (20 chicks/ replication).Chicks were reared for 6 weeks and divided at 2 week old into the following treatments:1st treatment (G1): Ad libitum feeding (control), 2nd, 3rd and 4th treatments (G2, G3 and G4): quantitative feed restriction (30%), 5th, 6th and 7th treatments (G5, G6 and G7): time feed rectriction (12 hours/day), 8th , 9th and 10th treatments (G8, G9 and G10): diet dilution with sand (15%). 1% of fenugreek powder was added to G3 , G6 and G9 diets and 1% of anise powder was added to G4, G7 and G10 diets. The results revealed that all feed restriction treatments led to maintain accumulatively (1- 6 weeks) the body weight, weight gain and growth rate accompanied with lowering (P<0.05) feed intake and improve (P<0.05) feed conversion coefficient . It was also found that each treatment has special role in its positive effect for these traits during the feed restriction and compensatory growth stages. Moreover, there was a significant increase (P<0.05) in dressing percentage with and without edible viscera expect G5 and high increase (P<0.05) in productive index in G3. Most of the improvement in these mentioned traits was achieved in feed restriction diets enriched with fenugreek and anise seed powders.